Examining the determinants of resilience and mental stress in emergency department nurses - Zahra Kamari; Ali Akbar Vaisi Raygani; Nader Salari; Behnam Khaledi-Paveh; Mohammad Mehdi Mohammadi (BMC Nursing)
Abstract Background Emergency departments (ED) are characterized by highly dynamic environments. This study aimed to identify determinants of resilience and mental stress among ED nurses. Methods A cross-sectional, analytical design was employed to assess 316 emergency nurses in Kermanshah hospitals using a convenience sampling method. The Connor-Davidson Resilience Scale and the Perceived Stress Scale measured resilience and mental stress, respectively. Data were analyzed using independent t-tests, ANOVA, chi-square tests, and Pearson’s correlation in SPSS version 25. Results The average mental stress score was 26.9, and the average resilience score was 64, indicating moderate levels. Significant relationships were found between employment status, emergency responsibility, economic status, and resilience (P < 0.01). Additionally, place of residence, number of children, education, shift work, social network presence, employment status, emergency responsibility, and economic status were significantly related to psychological stress (P < 0.01). Pearson’s correlation showed an inverse relationship between resilience and mental stress (r = -0.123, P = 0.029). Age was inversely related to mental stress (r = -0.408, P < 0.001), while overtime hours per month were directly related to resilience (r = 0.135, P = 0.016) and inversely related to mental stress (r = -0.482, P = 0.029). Conclusion The research highlights the importance of considering demographic variables in managing nurses’ resilience and mental pressure, emphasizing the need for hospital officials to focus on work shifts, employment status, and economic conditions.